Evolution and dispersal of St. Louis encephalitis virus in the Americas. - Auguste, A; Pybus, O; Carrington, C (2009)
Using a Bayesian coalescent approach on a dataset of 73 envelope gene sequences we estimated substitution rates and dates of divergence for St. Louis encephalitis virus (SLEV) in the Americas. We found significant rate heterogeneity among lineages, such that "relaxed" molecular clock models were much better supported than a strict molecular clock. The mean substitution rate estimated for all SLEV was 4.1x10(-4)substitutions/site/year (95% HPD 2.5-5.7)-higher than previous estimates that relied on the less well-suited strict clock. Mean substitution rates for individual lineages varied from 3.7x10(-4) to 7.2x10(-4)substitutions/site/year. For the first time we also assessed the magnitude and direction of viral gene flow within the Americas. The overall direction of gene flow during the period represented by the phylogeny is from South to North, and the region between 15 degrees N and 30 degrees N latitude appears to be the major source of virus for the rest of North America, which is consistent with migratory birds returning to their northern breeding grounds having acquired infection while wintering in the region of the Gulf of Mexico.